Anomalia gravimétrica do flanco sul do alto estrutural de Pau D'Alho - Hammerle, Roberto Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work present the results from a geophysical survey (gravimetric method) of the accentuated gravimetric anomaly between Pau d'Alho and Anhembi structural highs, in the geological context of the Northeast Limb of the Paraná Sedimentary Basin. The distinct characteristics of the structural highs region have made of this region a target for several studies that intend to comprehend these structures and to prospect oil. The great majority of the works in this region have as focus the fault's cinematic recognizement and the litologic/tectonic conditioning of these structures, lacking in subsurface studies. In the 125 km² area, it was used a closed gravimetric line spacing forming a mesh with equispaced stations in 1 500 m. After processing the data and comparing it with previuos studies, it was concluded that the analytical signal from the Butterworth's filter applied to the Bouguer anomaly is the filtering process that select the frequencies that best represent the geological settings described in the literature. Through the analyses of the relations between the gravimetric anomalies patterns and the geological structures previously mapped, geological models for the area were developed. The gravimetric information point to a structural configuration that could be explained by a NE-SW distensive stress field older than Serra Geral Formation

Este trabalho apresenta os resultados da investigação geofísica (método gravimétrico) da acentuada anomalia gravimétrica situada entre os Altos Estruturais de Anhembi e Pau D'Alho, no contexto geológico do Flanco Nordeste da Bacia do Paraná. As características distintas da região dos Altos Estruturais fizeram desta região o objeto de diversos estudos que visaram o entendimento destas estruturas e a prospecção de hidrocarbonetos. Grande parte dos trabalhos na região têm como enfoque o reconhecimento das cinemáticas das falhas e condicionamento litológico/tectônico dessas estruturas, carecendo de informações de subsuperfície. Na área de 125 km² foi utilizada a linha gravimétrica fechada formando uma malha de estações equidistantes em 1 500 m. Após o processamento dos dados e a comparação das informações de estudos anteriores, foi concluído que o sinal analítico do filtro Butterworth, aplicado sobre a anomalia Bouguer, é o processo de filtragem que seleciona as frequências que melhor representam a configuração geológica descrita na literatura. A partir da análise das relações entre os padrões das anomalias gravimétricas com as estruturas geológicas mapeadas foram confeccionados modelos geológicos da área. As informações gravimétricas indicam uma configuração estrutural para os blocos que poderia ser explicada por um campo de esforços distensivos segundo NE- SW, posterior Formação Serra Geral
Keywords: Geofisica; Georreferenciamento; Analise gravimetrica; Gravidade (Fisica) - Medição; Mapeamento geologico; Geologia estratigráfica; Paraná, Bacia